Modulated CH4 oxidation over PGM/Spinel oxide dual layer catalysts: Experiments and modeling - Pak Wing Chen; Jonathan Ratcliff; Lars C. Grabow; Michael P. Harold (Chemical Engineering Journal, 2025)

P02-25 Use of organotypic gingival cultures for nicotine pouch assessment - F. Zanetti; M. Alriquet; L. Ortega Torres; L. Neau; F. Maranzano; C. Pak; C. Mathis (Toxicology Letters, 2024)

Restless legs syndrome, periodic limb movements of sleep, and subclinical cardiovascular disease - Kevin J. Hochstrasser; Steven C. Rogers; Arshed Quyyumi; Dayna Johnson; Victoria Pak; Amit J. Shah; David B. Rye; Lynn Marie Trotti (Sleep and Biological Rhythms, 2024)

Revisiting mass, economic value, quality-based functional units in life cycle assessment of foods towards environmental benchmarking - N.-C. O; C.-J. Hwang; J.–S. Pak; Y.–I. Jon; I.–K. Ri; T.-H. Choe (International Journal of Environmental Science and Technology, 2024)

Multiscale phenological niches of seed fall in diverse A mazonian plant communities - Damie Pak; Varun Swamy; Patricia Alvarez‐Loayza; Fernando Cornejo‐Valverde; Simon A. Queenborough; Margaret R. Metz; John Terborgh; Renato Valencia; S. Joseph Wright; Nancy C. Garwood; Jesse R. Lasky (Ecology, 2023)
Phenology has long been hypothesized as an avenue for niche partitioning or interspecific facilitation, both promoting species coexistence. Tropical plant communities exhibit striking diversity in reproductive phenology, but many are also noted for large synchronous reproductive events. Here we study whether the phenology of seed fall in such communities is nonrandom, the temporal scales of phenological patterns, and ecological factors that drive reproductive phenology. We applied multivariate wavelet analysis to test for phenological synchrony versus compensatory dynamics (i.e., antisynchronous patterns where one species' decline is compensated by the rise of another) among species and across temporal scales. We used data from long‐term seed rain monitoring of hyperdiverse plant communities in the western Amazon. We found significant synchronous whole‐community phenology at multiple timescales, consistent with shared environmental responses or positive interactions among species. We also observed both compensatory and synchronous phenology within groups of species (confamilials) likely to share traits and seed dispersal mechanisms. Wind‐dispersed species exhibited significant synchrony at ~6‐month scales, suggesting these species might share phenological niches to match the seasonality of wind. Our results suggest that community phenology is shaped by shared environmental responses but that the diversity of tropical plant phenology may partly result from temporal niche partitioning. The scale‐specificity and time‐localized nature of community phenology patterns highlights the importance of multiple and shifting drivers of phenology.

Life cycle-carbon footprints for environmental performance/labeling of crop-based food products: analyses of complementary functional units and hotspots - N. C. O; S. C. Pak; R. J. Ri; H. I. Han (International Journal of Environmental Science and Technology, 2023)

Systems toxicology study reveals reduced impact of heated tobacco product aerosol extract relative to cigarette smoke on premature aging and exacerbation effects in aged aortic cells in vitro - Carine Poussin; Marco van der Toorn; Sophie Scheuner; Romain Piault; Athanasios Kondylis; Rebecca Savioz; Rémi Dulize; Dariusz Peric; Emmanuel Guedj; Fabio Maranzano; Celine Merg; Moran Morelli; et al. (Archives of Toxicology, 2021)
Aging and smoking are major risk factors for cardiovascular diseases (CVD). Our in vitro study compared, in the context of aging, the effects of the aerosol of Tobacco Heating System 2.2 (THS; an electrically heated tobacco product) and 3R4F reference cigarette smoke (CS) on processes that contribute to vascular pathomechanisms leading to CVD. Young and old human aortic smooth muscle cells (HAoSMC) were exposed to various concentrations of aqueous extracts (AE) from 3R4F CS [0.014–0.22 puffs/mL] or THS aerosol [0.11–1.76 puffs/mL] for 24 h. Key markers were measured by high-content imaging, transcriptomics profiling and multianalyte profiling. In our study, in vitro aging increased senescence, DNA damage, and inflammation and decreased proliferation in the HAoSMCs. At higher concentrations of 3R4F AE, young HAoSMCs behaved similarly to aged cells, while old HAoSMCs showed additional DNA damage and apoptosis effects. At 3R4F AE concentrations with the maximum effect, the THS AE showed no significant effect in young or old HAoSMCs. It required an approximately ten-fold higher concentration of THS AE to induce effects similar to those observed with 3R4F. These effects were independent of nicotine, which did not show a significant effect on HAoSMCs at any tested concentration. Our results show that 3R4F AE accelerates aging in young HAoSMCs and exacerbates the aging effect in old HAoSMCs in vitro, consistent with CS-related contributions to the risk of CVD. Relative to 3R4F AE, the THS AE showed a significantly reduced impact on HAoSMCs, suggesting its lower risk for vascular SMC-associated pathomechanisms leading to CVD.

Chemotherapy-Induced Cognitive Impairment Is Associated with Cytokine Dysregulation and Disruptions in Neuroplasticity - Dong-Dong Shi; Yu-Hua Huang; Cora Sau Wan Lai; Celia M. Dong; Leon C. Ho; Ed X. Wu; Qi Li; Xiao-Min Wang; Sookja Kim Chung; Pak Chung Sham; Zhang-Jin Zhang (Molecular Neurobiology, 2019)

Whole-genome sequencing data-based modeling for the investigation of an outbreak of community-associated methicillin-resistant Staphylococcus aureus in a neonatal intensive care unit in Hong Kong - Vincent C. C. Cheng; Shuk-Ching Wong; Huiluo Cao; Jonathan H. K. Chen; Simon Y. C. So; Sally C. Y. Wong; Siddharth Sridhar; Kwok-Yung Yuen; Pak-Leung Ho (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Actionable secondary findings from whole-genome sequencing of 954 East Asians - Clara Sze-man Tang; Saloni Dattani; Man-ting So; Stacey S. Cherny; Paul K. H. Tam; Pak C. Sham; Maria-Mercè Garcia-Barcelo (Human Genetics, 2018)

Central not peripheral vestibular processing impairs gait coordination - Yoav Gimmon; Jennifer Millar; Rebecca Pak; Elizabeth Liu; Michael C. Schubert (Experimental Brain Research, 2017)

The Asia-Pacific’s role in the emerging solar geoengineering debate - Masahiro Sugiyama; Shinichiro Asayama; Atsushi Ishii; Takanobu Kosugi; John C. Moore; Jolene Lin; Penehuro F. Lefale; Wil Burns; Masatomo Fujiwara; Arunabha Ghosh; Joshua Horton; Atsushi Kurosawa; et al. (Climatic Change, 2017)

Rapid Antimicrobial Susceptibility Testing with Electrokinetics Enhanced Biosensors for Diagnosis of Acute Bacterial Infections - Tingting Liu; Yi Lu; Vincent Gau; Joseph C. Liao; Pak Kin Wong (Annals of Biomedical Engineering, 2014)

Secondary cell wall composition and candidate gene expression in developing willow (Salix purpurea) stems - Yongfang Wan; Cristina Gritsch; Theodora Tryfona; Mike J. Ray; Ambrose Andongabo; Keywan Hassani-Pak; Huw D. Jones; Paul Dupree; Angela Karp; Peter R. Shewry; Rowan A. C. Mitchell (Planta, 2014)

Erratum to: RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2014)

RET and NRG1 interplay in Hirschsprung disease - Hongsheng Gui; Wai-Kiu Tang; Man-Ting So; Petroola Proitsi; Pak C. Sham; Paul K. Tam; Elly Sau-Wai Ngan; Stacey S. Cherny; Maria-Mercè Garcia-Barceló (Human Genetics, 2013)

Evaluating the effective numbers of independent tests and significant p-value thresholds in commercial genotyping arrays and public imputation reference datasets - Miao-Xin Li; Juilian M. Y. Yeung; Stacey S. Cherny; Pak C. Sham (Human Genetics, 2012)

A naturalistic study of grey matter volume increase after early treatment in anti-psychotic naïve, newly diagnosed schizophrenia - Michelle Y. Deng; Gráinne M. McAlonan; Charlton Cheung; Cindy P. Y. Chiu; Chi W. Law; Vinci Cheung; Pak C. Sham; Eric Y. H. Chen; Siew E. Chua (Psychopharmacology, 2009)

Antimicrobial fragments of the pro-region of cathelicidins and other immune peptides - Rachel C. Anderson; Maren Rehders; Pak-Lam Yu (Biotechnology Letters, 2008)

Confirmation of linkage to chromosome 1q for spine bone mineral density in southern Chinese - Ching-Lung Cheung; Qing-Yang Huang; Mandy Y. M. Ng; Vivian Chan; Pak C. Sham; Annie W. C. Kung (Human Genetics, 2006)

Evolution of Novel O-methyltransferases from the Vanilla planifolia Caffeic Acid O-methyltransferase - Huaijun Michael Li; David Rotter; Thomas G. Hartman; Fulya E. Pak; Daphna Havkin-Frenkel; Faith C. Belanger (Plant Molecular Biology, 2006)

Inferring establishment histories in populations of Quercus dentata (Fagaceae) from the analysis of spatial genetic structure - M. Y. Chung; K.-J. Kim; J.-H. Pak; C.-W. Park; B.-Y. Sun; E. R. Myers; M. G. Chung (Plant Systematics and Evolution, 2005)

Acute and Subchronic Toxicity of the Heavy Metals Copper, Chromium, Nickel, and Zinc, Individually and in Mixture, to the Freshwater Copepod Mesocyclops pehpeiensis - C. K. Wong; A. P. Pak (Bulletin of Environmental Contamination and Toxicology, 2004)

Expression of the translational repressor NAT1 in experimental models of cardiac hypertrophy - S. Jeson Sangaralingham; Brian J. Pak; M. Yat Tse; Ekaterini Angelis; Michael A. Adams; C. Smallegange; Stephen C. Pang (Molecular and Cellular Biochemistry, 2003)

Aerobic reduction of manganese oxide by Salmonella sp. strain MR4 - K.-R. Pak; O.-Y. Lim; H.-K. Lee; S.-C. Choi (Biotechnology Letters, 2002)

Molecular cloning and developmental expression of rat glycogenin in cardiac tissue - Brian J. Pak; S. Jeson Sangaralingham; Stephen C. Pang (Molecular and Cellular Biochemistry, 1999)